Acanthus ilicifolius Methanolic Extract for Oral Candidiasis Treatment through Tongue Epithelial STAT3 and Cell Death Evaluation - Revianti, Syamsulina; Andriani, Dwi; Pargaputri, Agni Febrina; Hartono, Mardiyanto Riski (European Journal of Dentistry, 2023)
Objectives This study aimed to evaluate the effects of topical application of Acanthus ilicifolius methanolic extract on signal transducer and activator of transcription 3 (STAT3) expression and tongue epithelial cell death caused by oral candidiasis under immunosuppressive conditions.Materials and Methods To obtain the oral candidiasis model, 20 healthy male Rattus norvegicus (Wistar) rats were administered oral dexamethasone and tetracycline for 14 days and oral candidiasis was induced with Candida albicans (ATCC-10231) 1 McFarland. They were then randomized into four groups—immunosuppression (K-), oral candidiasis (K + ), nystatin treatment (P1), and 20% A. ilicifolius methanolic extract treatment (P2) and were treated for 14 days. Histological analyses of cell death and candida invasion and immunohistochemical analysis of STAT3 in epithelial cells were performed.Statistical Analysis Epithelial cell death data were analyzed using one-way analysis of variance (ANOVA) and the post hoc Games–Howell test (p < 0.05) and STAT3 expression with one-way ANOVA and the post hoc least significant difference test (p < 0.05).Results Cell death was significantly different between K- and K+ and between K+ and P1 and P2 (p < 0.05); there were no significant differences between K- and P1 and P2 and between P1 and P2 (p > 0.05). STAT3 expression was significantly different between K- and P1 and P2 and between K+ and P1 and P2 (p < 0.05), but there were no significant differences between K+ and K- and between P1 and P2 (p > 0.05).Conclusion Topical administration of A. ilicifolius methanol extract increased STAT3 expression and decreased tongue epithelial cell death caused by oral candidiasis.
Keywords: cell death; STAT3; immunosuppression; oral candidiasis; corticosteroids; antifungals